Professional Identity of 0.24 Million Medical Students in China Before and During the COVID-19 Pandemic: Three Waves of National Cross-Sectional Studies - Yu, Chen; Liu, Qiao; Wang, Weimin; Xie, Ana; Liu, Jue (Frontiers in Public Health, 2022)
Background Professional identity (PI) influences the doctor’s thoughts and behaviors, thus professional identity formation (PIF) plays an important role in medical students’ education. Major changes to the learning environment could impact PIF, however, the influence of the novel coronavirus disease 2019 (COVID-19) pandemic on medical students’ PI had confusing conclusions in previous studies. We aimed to compare PI of medical students by using the data from three waves of national cross-sectional surveys conducted in China in 2019, 2020 and 2021, and also to examine factors that influence PIF. Method We used data from the China Medical Student Survey (CMSS), which have conducted three national cross-sectional surveys. From 2019 to 2021, CMCC retrieved data on PI from a nationally representative sample of medical students from 33, 121 and 123 colleges, respectively. We analyzed the data using Chi-square test, analysis of variance, and multivariable logistic regression, according to sociodemographic characteristics, pre-university experience, college characteristics, and college experience. Results A total of 244040 medical students in China participated in the surveys. The overall score of PI increased from 3.80 in 2019 to 3.85 in 2021. Medical students with family medical background, high intrinsic and extrinsic motivation of major selection, teachers’ positive role model, and high personal comprehensive quality ranking were more likely to have higher PI (all p<0.05). The more attention students paid to the COVID-19 pandemic, the higher PI they would have (aOR 1.93, 95% CI 1.67-2.24 for more attention; aOR 2.31, 95% CI 2.00-2.68 for the most attention). However, parents’ participation on the front lines of COVID-19 pandemic negatively influenced the PI of medical students (aOR 0.72, 95% CI 0.57-0.93). Conclusions PI of medical students increased during the COVID-19 pandemic. The impact of the pandemic on PI was complex. To improve the PI of medical students, education sector, health sector and the society need to make concerted efforts.